REDUCTION KINETICS OF LEAD-RICH SLAG WITH CARBON IN THE TEMPERATURE RANGE OF 1073 TO 1473 K - Hou, Xinmei; Chou, Kuo-Chih; Zhao, Baojun (Journal of Mining and Metallurgy, Section B: Metallurgy, 2013)
Extensive experiments have been carried out on the reduction of lead-rich slag in graphite crucible at temperature range of 1073 to 1473K. The reduction kinetics was also compared between industrial sinters and synthetic slags. The extent of reduction was measured by the volume of CO-CO2 gas produced at a given temperature and time. It was found that, at a given temperature, the reaction rate between the slag and carbon was initially fast and then slow as the extent of the reaction increases. Only limited reaction between slag and carbon occurred at temperatures below 1173K. At temperatures above 1173K, the reaction rate increased significantly with increasing temperature. The reduction reaction was found to be mainly liquid-solid reaction, which was chemically controlled at initial stage and diffusion controlled at later stage. The apparent activation energy was calculated to be 83.8 kJ/mol at chemically controlled stage and 224.9 kJ/mol at diffusion controlled stage for reduction of industrial sinter. For the synthetic slag, the reaction activation energy was 102.9 kJ/mol at chemically controlled stage and 259.4 kJ/mol at diffusion controlled stage. The difference of the activation energy between industrial sinter and synthetic slag can be explained by the difference in their CaO/SiO2 ratios.